Erosion assessment in the middle Kali Gandaki (Nepal): A sediment budget approach - Fort, Monique; Cossart, Etienne (Journal of Nepal Geological Society, 2013)
Active mountains supply the largest sediment fluxes experienced on earth. At mountain range scale, remote sensing approaches, sediments provenance or stream power law analyses, collectively provide rough long-term estimates of total erosion. Erosion is indeed controlled by rock uplift and climate, hence by a wide range of processes (detachment, transport and deposition), all operating within drainage basin units, yet with time and spatial patterns that are quite complex at local scale. We focus on the Kali Gandaki valley, along the gorge section across the Higher Himalaya (e.g. from Kagbeni down to Tatopani). Along this reach, we identify sediment sources, stores and sinks, and consider hillslope int eractions with valley floor, in particular valley damming at short and longer time scales, and their impact on sediment budgets and fluxes. A detailed sediment budget is presented, constrained by available dates and/or relative chronology, ranging from several 10 kyr to a few decades. Obtained results span over two orders of magnitude that can best be explained by the type and magnitude of erosional processes involved. We show that if large landslides contribute significantly to the denudation history of active mountain range, more frequent medium to small scales landslides are in fact of primary concern for Himalayan population.